Impact of atmospheric stability on wind turbine wake evolution. Issue 176 (May 2018) - Subramanian, B.; Chokani, N.; Abhari, R.S.
Abstract: The wakes of two wind turbines located at two different sites in flat terrain, one with neutral and one with unstable atmospheric conditions are described. Measurements with high spatial and temporal resolution are made with an instrumented drone that is equipped with a suite of sensors. These measurements for the first time detail at full-scale Reynolds number conditions and at both unstable and neutral atmospheric conditions, the wind speed and turbulent kinetic energy evolution in near- and far-wakes (up to six-diameters) including their vertical profiles at eleven different locations downstream. The dissipation rate of turbulent kinetic energy – obtained from wave number spectra measured in the inertial sub-range – is also reported for the different atmospheric stability conditions. Comparisons of these measurements to the recently developed wake prediction model highlight how these measurements can support further development of wake models. Highlights: Wake evolution downstream of a wind turbine located in a flat terrain is described. Measurements under neutral and unstable stratification at two different sites. Details for first time wind speed, TKE profiles at eleven different downstream locations. Dissipation rate of TKE obtained from wave number spectra is tabulated. Measurements compared to recently developed wake prediction model.